Experimental investigation of TRM-strengthened RC columns under concentric and eccentric axial loads - Erbas, Yas Ar Ar; Baran, Mehmet; Anıl, Özgür; Mercimek, Ömer (Elsevier Sci Ltd, 2025)
This study investigates the structural performance of reinforced concrete (RC) columns strengthened with textilereinforced mortar (TRM) under concentric and eccentric axial loads. A total of eighteen half-scale RC columns were tested to examine the influence of TRM strip width, strip spacing, and the use of CFRP fan-type anchors on key performance indicators, including load-carrying capacity, initial stiffness, displacement ductility, and energy dissipation. The experimental results showed that TRM confinement significantly enhanced both strength and stiffness, with these improvements being more pronounced under eccentric loading. Increasing the TRM strip width from 50 mm to 100 mm resulted in moderate gains in load capacity and stiffness, while reducing the strip spacing led to a clearer enhancement, particularly under combined axial and bending effects. Among the parameters studied, the incorporation of mechanical anchorage proved most effective, delivering up to 32 % higher load capacity under concentric loading and 18 % under eccentric loading, alongside substantial improvements in stiffness and better crack control. However, slight reductions in ductility were observed with closer strip spacing and anchorage. These findings underscore the importance of carefully optimizing TRM design parameters, especially the implementation of mechanical anchors, to achieve a balanced improvement in strength, stiffness, and energy absorption without compromising deformation capacity. The outcomes offer practical insights for retrofitting RC columns, contributing to safer and more resilient structural systems.
Keywords: RC Columns; Strengthening; TRM; Axial Load; Uniaxial Bending